Surface modification of duplex stainless steel with SiC preplacement using TIG torch cladding - P.H., Lailatul; Maleque, Md. Abdul (2016)
Surface modification of duplex stainless steel is important to make this material suitable for tribology and high temperature applications. The surface modification using fine SiC (20µm) powder preplacement by TIG torch technique has been developed on the surface of duplex stainless steel. The TIG torch was conducted with varying operating welding variables such as welding current of 80 A, 90 A ,100 A and energy input of 648, 768 and 1440 J/mm. The composite surface layer was characterized using Vickers micro-hardness tester and scanning electron microscopy (SEM). Based on the experimental results, it was found that re-solidified composite layer produced maximum hardness of 833.6 Hv0.5kgf from substrate hardness of 250 Hv0.5kgf for TIG processed of 768 J/mm (90A). The microstructure revealed the formation of dendrite phase due to complete melting of SiC in the modified layer. The formation of dendrites contributes to the increasing of hardness of this material.